Assessment of coastal ecological restoration effectiveness using an improved remote sensing ecological index: a case study of the Liaohe Estuary - Zhang, Yujia; Lu, Wenhai; Liu, Zhaoyang; Xu, Yan; Yang, Lu; Zeng, Rong (Frontiers in Ecology and Evolution, 2025)
IntroductionCoastal ecosystems are experiencing rapid degradation and biodiversity loss, driving large-scale restoration efforts, particularly in China. Traditional methods for evaluating restoration outcomes are often limited by high costs and restricted spatial coverage.MethodsThis study introduces an Improved Remote Sensing Ecological Index (IRSEI), which incorporates a salinity-sensitive component into the conventional RSEI framework to better capture the complexity of coastal zones.ResultsApplied to the Liaohe Estuary over ten years (2014–2024) using six Landsat 8 images, the index revealed a 23% increase in mean ecological quality and improvements across 48.3% of the area. The spatial recovery exhibited a “core-to-edge” pattern, with gains exceeding 0.2 in restored regions.DiscussionThe results underscore the index's utility as a cost-effective and scalable tool for monitoring coastal wetland restoration and supporting adaptive management in transitional ecosystems.